Lectoryn in the literal level of reading comprehension of high school students - Rosadio Vega, Yngrid Marlene (2019)
One of the most critical and still unsolved problems is the low reading comprehension of texts in Peruvian high school students. This critical problem has been corroborated by international tests such as PISA (2015, 2018) and a variety of studies by researchers who have become aware of this worrying situation. In this scenario, the present research study aims to establish whether the Lectoryn module had any influence on literal reading comprehension of texts in students in the first year of Basic Regular Education. In order to achieve this objective, the study used a quantitative approach and a quasi-experimental design. As data collection instruments, tests (pre-test and post test) were used on an intact sample of 51 students (control group, n=24; and experimental group, n=27). The results showed that in the pre-test both groups were at the Initial level and, after the implementation of the Lectoryn module, the experimental group improved to the level of expected achievement, whereas the control group did not. For contrasting the hypothesis, the Mann–Whitney U test was used, which showed, statistically, that there were no significant differences in the pre-test between the two groups, whereas, in the post test, there were evident differences.